Contagion nichts verbreitet sich schneller als Angst - Martinez, Cliff 1954- (Warner Bros. Entertainment, 2012)
A thriller centered on the threat posed by a deadly disease and an international team of doctors contracted by the CDC to deal with the outbreak
Bildformat 1.78:1 (16:9) geeignet für alle Bilschirmformate
Orig.: USA, Vereinigte Arabische Emirate 2011
Enth. Contagion: wie ein Virus die Welt verändert
Keywords: Centers for Disease Control and Prevention (U.S.) -- Drama.; Centers for Disease Control and Prevention; Epidemics -- Drama.; Communicable diseases -- Drama.; Epidemiologists -- Drama.; Thrillers (Motion pictures); Science fiction films.; Disaster films.; Feature films.; Epidemie; Thriller; Infektionskrankheit; Katastrophenfilm; USA; Film; DVD-Video